2018
DOI: 10.1021/acs.jpcc.8b05616
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laser Pulses Induced Insulator–Metal Transition and Multiple Plasmons in Barium Titanate Quantum Dots

Abstract: Recently, all-inorganic perovskite quantum dots have become a hot research topic due to their unique optical response. We have studied barium titanate quantum dots and their hybrid structure consisting silver (Ag) nanowires interacting with ultrafast laser pulses based on time-dependent density functional theory (TDDFT). Through controlling the wavelength and intensity of incident ultrafast light pulses, insulator–metal transition and long-wavelength plasmons can be induced in barium titanate quantum dots. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…In order to further understand the electron transition behavior of the QDs under external laser pulses, we calculate the excited state to investigate the changes in the electron occupied state. The wavelength of 792 nm is employed for ultrafast laser with the intensity of 2.0 eV Å À1 , which has been widely used in previous studies, 27,53 as shown in Fig. 5 (Cm-QDs, ppPv-Pnma-QDs, and I4mm-QDs) at about 2.48 fs, implying that R3m-QDs have a better optical response.…”
Section: Optical Responses Under the Certain Ultrafast Laser In Csgec...mentioning
confidence: 99%
See 3 more Smart Citations
“…In order to further understand the electron transition behavior of the QDs under external laser pulses, we calculate the excited state to investigate the changes in the electron occupied state. The wavelength of 792 nm is employed for ultrafast laser with the intensity of 2.0 eV Å À1 , which has been widely used in previous studies, 27,53 as shown in Fig. 5 (Cm-QDs, ppPv-Pnma-QDs, and I4mm-QDs) at about 2.48 fs, implying that R3m-QDs have a better optical response.…”
Section: Optical Responses Under the Certain Ultrafast Laser In Csgec...mentioning
confidence: 99%
“…Perovskite QDs can possess different optical absorption abilities under various wavelength lasers. Here, a wide range of laser wavelengths, 355, 476, 531, 654, and 792 nm, which are frequently employed in experiments and theories, 27 as well as the intensity of 1.5 eV Å À1 are selected shown in Fig. S5(a) (ESI †).…”
Section: Optical Properties Regulated By Ultrafast Laser For Csgecl 3...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the interaction of perovskite QDs with ultrafast laser pulses demonstrates interesting phenomena. Studies of BaTiO 3 QDs discovered an insulator–metal transition under ultrafast laser pulses, which is attributed to the breaking bonds of the Ba–O atoms under a sufficiently strong laser field . In addition, the optical response of perovskite QDs coupled with Ag nanowires shows strong optical absorption, demonstrating that perovskite QDs are great optical gain materials .…”
Section: Introductionmentioning
confidence: 99%